Anxious Vigilance – An investigation of the relationship between Optimal Managerial Ownership and Firm Value on the JSE - Muhlarhi , Tiniso Willie (University of the Witwatersrand, Johannesburg, 2022)
Managerial ownership has been advanced as a more effective corporate governance mechanism in minimising agency related costs by aligning the interests of managers with those of shareholders. This study examines the effects of equity ownership, using different ownership groups, on firm value of firms listed in the South African stock exchange to ascertain whether equity ownership results in well governed firms with higher firm value over the period of 2010 to 2020. The results are largely consistent with those in emerging markets, the results document that there is no statistically significant direct relationship between equity ownership and firm value. M ore so deviations from optimal equity ownership, both below and above optimal equity ownership, does not reduce firm value. The results also show that a portfolio of ownership firms (which refers to firms in which CEOs, the Executive Team, and Insiders (general employees) have equity ownership in the firm) outperforms a portfolio of non-ownership firms over the period 2015-2020, this aspect is more consistent to results reported in developed markets. Overall, managerial ownership does not appear to be an effective mechanism to aligning interest of shareholders and their managers in the South African landscape, other alternatives such as debt are proposed
A research report submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Commerce (50%) in Finance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Optimal Managerial Ownership; Agency Theory; CEO Ownership; Behavioral Agency Cost Explanations; UCTD; SDG-8: Decent work and economic growth